ChemInform Abstract: Bromenium‐Catalyzed Tandem Ring Opening/Cyclization of Vinylcyclopropanes and Vinylcyclobutanes: A Metal‐Free [3 + 2 + 1]/[4 + 2 + 1] Cascade for the Synthesis of Chiral Amidines and Computational Investigation. Issue 10 (7th March 2013) - Ganesh, Venkataraman; Sureshkumar, Devarajulu; Chanda, Debasree; Chandrasekaran, Srinivasan
Abstract This is a versatile method for highly stereoselective preparation of bicyclo[4.4.0]‐, [4.3.0]‐ and [4.3.1] amidines.